Minimizing the difference of two quasiconvex functions over a vector-valued quasiconvex system. (3rd May 2020) - Dempe, Stephan; Gadhi, Nazih Abderrazzak; Hamdaoui, Khadija
Abstract : The article is concerned with an optimization problem P where we minimize the difference of two quasiconvex scalar functions under a vector-valued quasiconvex system. Using the Q-subdifferential introduced by Suzuki and Kuroiwa [Optimality conditions and the basic constraint qualification for quasiconvex programming. Nonlinear Anal. 2011;74:1279–1285], together with a special constraint qualification, we give necessary optimality conditions to P .